Nonintubated thoracoscopic lung resection: a 3-year experience with 285 cases in a single institution - Chen, Ke-Cheng; Cheng, Ya-Jung; Hung, Ming-Hui; Tseng, Yu-Ding; Chen, Jin-Shing (Journal of Thoracic Disease, 2012)
Objective: Tracheal intubation with one-lung ventilation is considered mandatory for thoracoscopic surgery. This study reported the experience of thoracoscopic lung resection without endotracheal intubation in a single institution. Methods: From August 2009 through July 2012, 285 consecutive patients were treated by nonintubated thoracoscopic surgery using epidural anesthesia, intrathoracic vagal blockade, and sedation for lobectomy, segmentectomy, or wedge resection in a tertiary medical center. The feasibility and safety of this technique were evaluated. Results: The final diagnosis for surgery were primary lung cancer in 159 patients (55.8%), metastatic lung cancer in 17 (6.0%), benign lung tumor in 104 (36.5%), and pneumothorax in 5 (1.8%). The operative methods consisted of conventional (83.2 %) and needlescopic (16.8%) thoracoscopic surgery. The operative procedures included lobectomy in 137 patients (48.1%), wedge resection in 132 (46.3%), and segmentectomy in 16 (5.6%). Collapse of the operative lung and inhibition of coughing were satisfactory in most of the patients. Fourteen (4.9%) patients required conversion to tracheal intubation because of significant mediastinal movement [5], persistent hypoxemia [2], dense pleural adhesions [2], ineffective epidural anesthesia [2], bleeding [2], and tachypnea [1]. One patient (0.4%) was converted to thoracotomy because of bleeding. No mortality was noted in our patients. Conclusions: Nonintubated thoracoscopic lung resection is technically feasible and safe in selected patients. It can be a valid alternative in managing patients with pulmonary lesions.